On the genus Diadocidia (Diptera, Sciaroidea, Diadocidiidae) in Costa Rica - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2007)
The genus Diadocidia Ruthe is shown for the first time to be present in Costa Rica. Three species were found: Diadocidia nigripalpis Edwards, hitherto known to occur in the south of Brazil, and two new species, hybrida and similis. While nigripalpis is confirmed to belong to the subgenus Adidocidia Laštovka & Matile, both hybrida and similis cannot be classified on a subgeneric level, since their morphology includes features typical of both Diadocidia s. str. and Adidocidia. A key is provided to the Costa Rican species of Diadocidia.